Introducing mesoporosity in zeolite 4A bodies for Rapid CO2 capture. Issue 40 (September 2020) - Panda, Debashis; Kumar, E. Anil; Singh, Sanjay Kumar
Graphical abstract: Highlights: Hierarchical zeolite 4A (HZ4A) is synthesized for enhanced CO2 capture performance. HZ4A displays tunable physicochemical characteristics with improved surface area and enhanced mesopore volume. HZ4A offers rapid gas diffusion within the pores, low water adsorption capacity and low CO2 heat of adsorption. HZ4A exhibits excellent CO2 adsorption stability and low CO2 regeneration energy. Abstract: In this study, we introduced mesoporosity by post-synthesis modification of binder-containing zeolite 4A (Z4A) bodies using urea treatment, to synthesize hierarchical zeolite 4A (HZ4A) with tailored textural properties. Hierarchical zeolite 4A such as HZ4A-1−3, HZ4A-1−1, and HZ4A-3−1 were synthesized by varying the urea to zeolite weight ratio as 1:3, 1:1, and 3:1 respectively. The synthesized HZ4A displayed tunable physicochemical characteristics, where HZ4A-1−3 exhibited improved surface area (126 m 2 g −1 ), enhanced mesopore volume (0.44 cm 3 g −1 ) and co-existence of both micro ( ca. 0.4 nm) and mesopores (5.5 nm). HZ4A-1−3 also exhibited enhanced CO2 adsorption performance even when exposed to moisture at 1 bar and 40 °C. Moreover, HZ4A-1−3 displayed excellent CO2 adsorption stability over ten consecutive adsorption-desorption cycles. The presence of mesopores in HZ4A-1−3 facilitated rapid gas diffusion within the pores during both adsorption (29 s faster) and desorption (92 s faster), low water adsorption capacity (20 % lesser), mild desorption temperature (13 °C lesser) and low CO2 heat of adsorption (14 % lesser) as compared to Z4A bodies, and hence achieved better CO2 adsorption efficacy for HZ4A-1−3 with reasonable CO2 regeneration energy. These results suggested the potential of hierarchical zeolite 4A (HZ4A) as a cost-effective sorbent for post-combustion CO2 capture application.